The Nigerian Oil and Gas Industry Content Development Act and GATT Treaty Obligations: On a Path of Harmony or Discord? - Orji, Uchenna Jerome (Latin American Journal of Trade Policy, 2020)
The Nigerian Oil and Gas Industry Content Development Act of 2010 prescribe local content requirements to promote the patronage of Nigerian products and services by operators in the oil and gas industry. Local content requirements however appear to violate obligations under the World Trade Organization’s (WTO) General Agreement on Tariffs and Trade (GATT) (1994) of which Nigeria is a member. This article examines provisions of the Act and Nigeria’s obligations under the GATT with a view to determining whether the provisions of the Act are in violation of GATT obligations, and whether those violations are covered by any of the exemptions under the GATT. The article finds that sections 10(1) (a), 11(1), 12 and 13 of the Act, which favor the use of local products and materials for projects in the oil and gas industry, contravene the national treatment obligations under Article III of GATT. The article also finds section 53 of the Act to be in violation of the obligation to ensure the general elimination of quantitative restrictions under Article XI:1 of GATT. However, the article suggests that GATT exemptions justify Nigeria’s application of local content measures in the industry. Nigeria can rely on Article XVIII of GATT to apply local content measures for the purpose of promoting economic development and improving living standards in the country. Besides, Nigeria can rely on Articles XII: 1/2 and XIX:1 of GATT to apply local content measures that restrict fabricated/welded metal products imports in order to prevent a serious decline in monetary reserves and also safeguard domestic producers of similar products from “serious injury” that may arise from the increased imports of such products.Keywords: GATT; Local content requirements; Nigeria; WTO obligations; Oil and gas industry.